156k views
5 votes
If 2x 2 + 13x – 7 = 0, then x could equal to which of the following?

User KevinTale
by
3.6k points

2 Answers

0 votes

Answer:

x = 1/2 and x = -7

Step-by-step explanation:

you need to factor

multiply 2 x -7 to get -14

then find factors of -14 that add to give you 13

14 and -1 work

now rewrite the original equation but replace 13x with 14x - 1x

so 2x^2 + 14x - 1x -7 = 0

now factor by grouping

(2x^2 + 14x) (-1x - 7) = 0

factor the greatest common factor out of each group

2x(x + 7) -1(x + 7) = 0

the factors are (2x - 1) (x + 7) = 0

set each factor equal to zero and solve both for x

2x - 1 = 0 x + 7 = 0

+1 +1 - 7 - 7

2x = 1 x = -7

÷2 ÷2

x = 1/2

User Dilly B
by
3.4k points
4 votes

Answer:3/13

Step-by-step explanation:

User David Watts
by
3.5k points